Analisis Pengaruh BI Rate, Dana Pihak Ketiga (DPK) dan Rasio Non Performing Financing (NPF) terhadap Produk Pembiayaan dengan Akad Murabahah pada Bank Syariah di Indonesia - Rizal Fahlevi (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2016)
This study aims to examine and analyze financing product with murabahah contract of sharia bank in Indonesia. This research is important to do because murabahah is the most popular contract and dominate financing component of sharia bank in Indonesia. As for some of the factors analyzed in the influenced of murabahah are: BI Rate, third party funds and Non Performing Financing ratio (NPF). Data analysis methods used in this study is an analysis of Multiple Linier Regression. These result indicated that BI rate had a negative impact to murabahah and significant; third party funds had had a positive impact to murabahah and significant; Non Performing Financing ratio (NPF) had a negative impact to murabahah and significant. These three variables hese three variables jointly affect murabahah growth of 99.4%, while the remaining 0.6% is explained by other variables not included in the model.